Training in Sales and Capital for Micro, Small, and Medium Enterprises (UMKM) of Street Vendors in North Bekasi - Cristalyn (Yayasan Putra Adi Dharma, 2023)
This research aims to examine the impact of sales training on the capital of Micro, Small, and Medium Enterprises (UMKM) of street vendors in North Bekasi. UMKM street vendors play a vital role in the local economy but often face various challenges, including limited capital and intense competition. This research utilizes survey and interview methods to gather data from street vendors who have undergone sales training. The research results indicate that sales training has a positive impact on the capital of UMKM street vendors in North Bekasi. Training enhances the knowledge of street vendors regarding more effective sales strategies, financial management, and marketing. Additionally, the training also improves interpersonal skills and customer service, which, in turn, enhances the attractiveness of their businesses. This research provides recommendations to the government and relevant stakeholders to further support sales training for UMKM street vendors. Consequently, they can become more competent in dealing with increasing competition and developing their businesses with limited capital.